Pengaruh Adaptabilitas Karier dan Kepuasan Kerja Terhadap Job Hopping Pada Karyawan Generasi Milenial di Kota Balikpapan - Ardani, Muhamat Ahyar; Rasyid, Miranti; Rahmah, Dian Dwi Nur (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
The phenomenon of job hopping refers to the voluntary behavior of frequently switching jobs or companies, which is often done by the millennial generation in their workplaces. Therefore, this study aims to explore this phenomenon by examining the influence of career adaptability and job satisfaction on job hopping among millennial employees, particularly in Balikpapan City. This research uses a quantitative approach. The data analysis technique employed is multiple linear regression. The subjects of this study are 70 millennial employees in Balikpapan City, selected using purposive sampling. The data collection methods used are career adaptability, job satisfaction, and job hopping scales. The research reveals no substantial impact of career adaptability and job satisfaction on job-hopping behavior among millennial employees in Balikpapan. The findings indicate that these variables only minimally account for variations in job-hopping tendencies. Measurements place job-hopping tendencies, career adaptability, and job satisfaction at low levels, suggesting that employees show a limited inclination to switch jobs, coupled with low adaptability and satisfaction. These insights guide company management toward understanding job-hopping dynamics more effectively. While job satisfaction and career adaptability show little influence, fostering a positive work environment and improving employee satisfaction remain vital strategies for minimizing job-hopping. The study also points to the possibility of other, more impactful factors influencing job-hopping that warrant further investigation.